Analysis of spatial distribution of malaria in the department of Chocó for the year 2016 (2018)
(Eng) The present investigation has as purpose the estimation of a generalized linear spatial regression model of Poisson distribution that allows to explain the geographic-spatial behavior of malaria for the department of Chocó for the year 2016. The probability maps were the result of statistical techniques spatial data type Lattice such as criteria of figures, distances and physical contiguity, in order to determine the existence of a spatial relationship of the disease in question. To verify this spatial autocorrelation among the municipalities of the department of Chocó, it was carried out based on the statistical interaction of sanitary, environmental and demographic variables such as the population of each municipality. However, it was necessary to perform a Gaussian anamorphosis process to guarantee the normalization of the data in standardized morbidity rates (SMR) and thus identify the statistical structure of the data that for this year were from a Poisson distribution. The study allowed the identification of positive spatial autocorrelation in some municipalities of Chocó, such as Paimado, Istmina and Tado, where ma - laria is more likely to occur due to its municipal proximity according to the physical relationship of certain study variables. It was obtained as a result that the variables that best explain malaria in the Chocó municipalities are the coverage of forests and unsatisfied basic needs that give as a product the map of spatial autocorrelation and the map of probability of occurrence among the municipalities of the department.